Pertanggungjawaban Hukum Penyelenggara Sistem Elektronik User Generated Content terhadap Penyebaran Iklan Judi Online Berdasarkan Ketentuan Hukum Siber di Indonesia - Nicholas Kevin Yolianto; Enni Soerjati Priowirjanto; Nella Sumika Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the rampant spread of online gambling advertisements in Indonesia, which contravenes the Criminal Code (KUHP) and Law No. 11 of 2008 on Electronic Information and Transactions (UU ITE) and its amendments, which prohibit gambling. Law enforcement faces significant challenges, one of which stems from the self-regulatory policies of Electronic System Operators (ESOs) for User-Generated Content (UGC), which do not fully prohibit online gambling advertisements. The objective of this study is to analyze the spread of such advertisements and the legal framework governing ESOs for UGC based on cyberlaw provisions. The methods used include a normative legal approach to examine principles, theories, and legal history, as well as a sociological legal approach utilizing secondary data through the integration of legal and social sciences. This research is descriptive-analytical, using data from literature reviews and semi-structured interviews. The results of the study indicate that the spread of online gambling advertisements is driven by the advertising features of PSE UGC and the weak effectiveness of existing self-regulatory policies. Additionally, the government is deemed to have been lenient in imposing administrative, criminal, or civil sanctions on PSE UGC, exacerbated by the ambiguous provisions of the Criminal Code (KUHP) and the ITE Law regarding gambling regulations. The research recommendations are for the government to pressure PSE UGC to strengthen internal policies regarding the prohibition of online gambling content, enforce administrative sanctions strictly, and revise ambiguous phrases in the Criminal Code and ITE Law to clarify regulations and strengthen law enforcement efforts against the spread of online gambling advertisements in Indonesia.